Competition between Ammonia-Oxidizing Bacteria and Benthic Microalgae - Risgaard-Petersen, Nils (American Society for Microbiology, 2004)
The abundance, activity, and diversity of ammonia-oxidizing bacteria (AOB) were studied in prepared microcosms with and without microphytobenthic activity. In the microcosm without alga activity, both AOB abundance, estimated by real-time PCR, and potential nitrification increased during the course of the experiment. AOB present in the oxic zone of these sediments were able to fully exploit their nitrification potential because NH(4)(+) did not limit growth. In contrast, AOB in the alga-colonized sediments reached less than 20% of their potential activity, suggesting starvation of cells. Starvation resulted in a decrease with time in the abundance of AOB as well as in nitrification potential. This decrease was correlated with an increase in alga biomass, suggesting competitive exclusion of AOB by microalgae. Induction of N limitation in the oxic zone of the alga-colonized sediments and O(2) limitation of the majority of AOB in darkness were major mechanisms by which microalgae suppressed the growth and survival of AOB. The competition pressure from the algae seemed to act on the entire population of AOB, as no differences were observed by denaturing gradient gel electrophoresis of amoA fragments during the course of the experiment. Enumeration of bacteria based on 16S rRNA gene copies and d-amino acids suggested that the algae also affected other bacterial groups negatively. Our data indicate that direct competitive interaction takes place between algae and AOB and that benthic algae are superior competitors because they have higher N uptake rates and grow faster than AOB.